Electrophoresis of electrostatically assembled fullerene-porphyrin conjugates - Hartnagel, Uwe; Balbinot, Domenico; Jux, Norbert; Hirsch, Andreas (Organic & Biomolecular Chemistry, 2006)
The formation of electrostatically coupled assemblies of a series of anionic dendritic fullerene derivatives and cationic porphyrins in buffered aqueous media was studied with gel electrophoresis. Of central interest in these investigations was the variation of the amount of charge carried by the molecules, their size, shape and self-aggregation. Ferric cytochrome c 1 and the more rigid zinc porphyrin 2 served as octacationic species. The two new anionic fullerene derivates 3 and 6 were synthesized. The formation of electrostatic complexes of the fullerene polyelectrolytes 3 and 4 with 1 and 2 was clearly evident in the gel electrophoresis experiment. Compounds 5 and 6 showed a similar behaviour towards 2. The electrophoresis experiments confirmed previous results obtained with other techniques on a qualitative level and gave new insights into aggregation phenomena. © The Royal Society of Chemistry 2006.